FACTORS ASSOCIATED WITH BEHAVIORS IN RESPONSE TO HEALTH-RELATED MESSAGING FROM SHAWNEE COUNTY HEALTH DEPARTMENT: RESULTS OF A CASPER SURVEY - Worthington, Amanda Jo (My University, 2017)
The effectiveness of Shawnee County Health Department’s (SCHD) “Dump Day” mosquito control campaign was evaluated using the Community Assessment for Public Health Emergency Response (CASPER) door-to-door survey method. The Dump Day campaign, which began during the summer of 2016, focused on emptying standing water on private property in effort to reduce mosquito breeding sites. CASPER is an epidemiologic technique designed to provide low cost, household based information about a community quickly and with limited resources. The primary objective of this project was to measure the effectiveness of SCHD’s Dump Day campaign by assessing associated variables; age, routes of health-messaging uptake, and mosquito prevention methods practiced by the public. In addition, CASPER was used to determine if this method is a useful tool for SCHD to evaluate other programs and campaigns. The development of this CASPER closely followed the toolkit provided by CDC. Sampling was conducting in two stages; stage one entailed randomly selecting 30 clusters within Shawnee County and stage two encompassed randomly selecting seven households within each cluster. With 30 clusters selected with a goal of seven household selected a total of 210 households were selected for interview. Of those, 117 interviews were successfully completed and 43 refusals were documented. SCHD employees and MRC volunteers achieved a 55.7% completion rate, a 73.1% cooperation rate, and a 40.6% contact rate for this CASPER. This study revealed that for those who were aware of the Dump Day campaign dumped water on personal property. Also, individuals at high risk of WNV complications and death, those 65 years of age or older, were less likely to dump water on their property, use mosquito repellent, and consider mosquito control a public health issue. Households with children residing in them were more likely to use mosquito repellent and consider mosquitoes to be a nuisance on their property.
Keywords: CASPER; Mosquito Survey